1983
DOI: 10.1083/jcb.96.4.1108
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of extracellular matrix by mouse trophoblast outgrowths: a model for implantation

Abstract: During implantation the embryo attaches to the endometrial surface and trophoblast traverses the uterine epithelium, anchoring in the uterine connective tissue. To determine whether trophoblast can facilitate invasion of the uterus by degrading components of normal uterine extracellular matrix, mouse blastocysts were cultured on a radio-labeled extracellular matrix that contained glycoproteins, elastin, and collagen. The embryos attached to the matrix, and trophoblast spread over the surface. Starting on day 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 28 publications
(43 reference statements)
1
42
1
1
Order By: Relevance
“…In fact, these enzymes may not need specific activators as they are autoacti-vated in vitro (Bergmann et al, 1995). Also, €-aminocaproic acid, a n inhibitor of plasminogen activators, does not inhibit rabbit blastocyst attachment or degradation of matrix by mouse trophoblasts in vitro (Denker, 1977;Glass et al, 1983) while inhibitors of metalloproteinases do so (Behrendtsen et al, 1992). It is therefore possible that the plasminogen activatorlplasmin system has an insignificant function in degradation of matrix components but could, alternatively, regulate fibrin formation in the area where maternal blood vessels are breached.…”
Section: Interplay Of Proteinases and Inhibitors At The Embryo Implanmentioning
confidence: 99%
“…In fact, these enzymes may not need specific activators as they are autoacti-vated in vitro (Bergmann et al, 1995). Also, €-aminocaproic acid, a n inhibitor of plasminogen activators, does not inhibit rabbit blastocyst attachment or degradation of matrix by mouse trophoblasts in vitro (Denker, 1977;Glass et al, 1983) while inhibitors of metalloproteinases do so (Behrendtsen et al, 1992). It is therefore possible that the plasminogen activatorlplasmin system has an insignificant function in degradation of matrix components but could, alternatively, regulate fibrin formation in the area where maternal blood vessels are breached.…”
Section: Interplay Of Proteinases and Inhibitors At The Embryo Implanmentioning
confidence: 99%
“…Previous studies have demonstrated that the degradation of the extracellular matrix by blastocyst outgrowth could be used as an in vitro model for embryo implantation (55,57). To directly assess the in vivo regulation of gelatinase (e.g.…”
Section: Defective Matrix Degradation By Rab11amentioning
confidence: 99%
“…1C). There was a large increase in the activity of proteinases, particularly the 92-kD gelatinase, during blastocyst outgrowth, a process corresponding to acquisition of invasiveness during implantation and early postimplantation development in vivo (Glass et al 1983). Cultured egg cylinder-stage embryos secreted even more of these proteinases.…”
Section: Mouse Embryos Secrete Functional Proteinasesmentioning
confidence: 99%